Ordenamento ferromagnético em poli(3-hexiltiofeno) à temperatura ambiente - Paula, Fernando Rogério de (Universidade Federal de São Carlos, 2009)
In this work we present, for the first time, a systematic study of magnetic properties of an alkyl derivative of thiophene: the poly(3-hexylthiophene) prepared in acetonitrile. This polymer was investigated in different preparation conditions, i.e., water concentration of the electrolyte solution, applied pressure in the pellets, growth and reduced potentials. The goal was the comprehension of magnetic phases in poly(3-hexylthiophene) and the development of a protocol for sample preparation. This procedure aims the control the magnetic properties. Magnetic measurements as a function of temperature and applied magnetic field performed in SQUID magnetometer show that the poly(3-hexylthiophene) exhibits a ferromagnetic phase at room temperature. Our results show that the ferromagnetic phase appears due to the exchange interaction between polaron in interchains. Experiments performed with samples stored in air and exposed at high temperature (400 K), show that the nice ferromagnetic behavior is reduced. These results discard the possibility of contamination by magnetic particles.
Ferromagnetic order in poly(3-hexylthiophene) at room temperature
Keywords: Magnetismo; Polímeros condutores; CIENCIAS EXATAS E DA TERRA::FISICA